Irregular Occupations and Environmental Impacts Caused by Fire of the Neighborhood of Educandos in the City of Manaus - Amazonas - dos Santos Leal, Lucivânia; Rocha Pinto, Fabiana; Sousa Martins Vilela, Fernanda; Barbosa de Alencar, David; de Freitas Lopes, Gisele (International Journal for Innovation Education and Research, 2019)
The paper describes the data of an exploratory research conducted after a fire that occurred in a favela space in the described Educandos neighborhood, located in the South Zone, peripheral area of ​​Manaus. Educandos was formed over 100 years ago, when the first families began housing construction. At first glance, walking through the main streets of the neighborhood, there is no evidence of the irregular situation of the place, because masonry structures cover the stilt houses, installed near the Rio Negro bed, an area affected by the fire. Assuming that irregular occupation contributed to the cause of the fire, the study aimed to carry out the impacts caused by the fire. Tracing a qualitative and quantitative diagnosis of these impacts, it was observed through the Interaction Matrix that the impacts were negative in nature, 85% directly, has as local scale, irreversible for impacts to vegetation and social problems, high magnitude during the action of fire.